2019
DOI: 10.18203/2320-6012.ijrms20194191
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study between flipped classroom and traditional lecture-based classroom in first year medical students

Abstract: Introduction: Flipped classroom is a new pedagogical model in which students are provided with study resource material to develop a basic understanding of the topic before class, and in-class precious time is used for learner-centric activities. Accordingly the study objectives were to compare the effect of flipped and traditional classroom teaching method and to determine the student’s perception of flipped and traditional teaching method.Method: This was a non-randomized experimental study. A detailed multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…In this case, it can be presumed that the finding of the study goes in line with the relevant literature and that the abovementioned approach positively influences the learning achievement of the postgraduate students. By contrast, some studies that compared flipped learning to other methods have stated that there are no significant differences or no significant increase is observed in learning performance (Arriaga & Talavera, 2018;Topal & Akhisar, 2018;Aggarwal, Thakur, Agrawal, Jhajharia, Madaan & Mahapatra, 2019;Leatherman and Cleveland, 2020). The reason behind the different results obtained by these studies in the literature could be attibuted to the different ways of implementation of flipped learning and the different flipped-learning-based activities carried out during the course.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In this case, it can be presumed that the finding of the study goes in line with the relevant literature and that the abovementioned approach positively influences the learning achievement of the postgraduate students. By contrast, some studies that compared flipped learning to other methods have stated that there are no significant differences or no significant increase is observed in learning performance (Arriaga & Talavera, 2018;Topal & Akhisar, 2018;Aggarwal, Thakur, Agrawal, Jhajharia, Madaan & Mahapatra, 2019;Leatherman and Cleveland, 2020). The reason behind the different results obtained by these studies in the literature could be attibuted to the different ways of implementation of flipped learning and the different flipped-learning-based activities carried out during the course.…”
Section: Discussionmentioning
confidence: 91%
“…Findings from several studies suggest that there are positive effects of flipped learning in the field of education (Polat & Karabatak, 2022;Nourinezhad, Hadipourfard & Baval, 2022;Jdaitawi, Hussein, Muhaidat, & Joudeh, 2022;Bergeson, 2022;Nja, Orim, Neji, Ukwetang, Uwe, & Ideba, 2021;Masadeh, 2021;Hava, 2021). By contrast, other studies have also emphasized the lack of any significant increase in learning performance (Arriaga & Talavera, 2018;Topal & Akhisar, 2018;Aggarwal, Thakur, Agrawal, Jhajharia, Madaan & Mahapatra, 2019;Leatherman & Cleveland, 2020).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Tanget al [2] found that fourth year medical students in the FC performed better on the posttest of ophthalmology when compared to those from the TC. Cabi [15] indicated that the use of the FC model didn"t have significant impact on the students" academic achievement compared to TC, and Aggarwal et al [16] who found that the mean assessment scores of first year medical students in biochemistry in the flipped and traditional classrooms were statistically insignificant and concluded that learning gain not affected by the method of teaching. Few studies only e.g., Gundlach et al [17] concluded that students in TC preformed significantly better than the students in FC.…”
Section: Discussionmentioning
confidence: 99%
“…According to Romero & Angeles (2023), participants in the flipped classroom are driven and like learning mathematics whereas the conventional approach has a detrimental impact on students' attitudes and lowers their motivation, self-confidence, and sense of enjoyment for mathematics. In flipped classroom, learner is more conscious and responsible of their learning process therefore may lead to positive results in the long run (Aggarwal et al, 2019). Makinde (2019) argued that Nigeria urgently needs a flipped classroom learning technique to overcome the low mathematics performance of kids and advance science and technology.…”
Section: Literature Reviewmentioning
confidence: 99%
“…key education stakeholders believe that new, creative approaches are needed to ensure that students and teachers are both more actively involved in the learning process. This can be accomplished by distributing lecture materials in advance and involving students in discussion during lecture time (Aggarwal et al, 2019).…”
Section: Introductionmentioning
confidence: 99%